2007
DOI: 10.1002/aris.2007.1440410114
|View full text |Cite
|
Sign up to set email alerts
|

Credibility: A multidisciplinary framework

Abstract: IntroductionThis chapter reviews the theoretical and empirical literature on the concept of credibility and its areas of application relevant to information science and technology, encompassing several disciplinary approaches. An information seeker's environment-the Internet, television, newspapers, schools, libraries, bookstores, and social networks-abounds with information resources that need to be evaluated for both their usefulness and their likely level of accuracy. As people gain access to a wider variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
218
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(245 citation statements)
references
References 198 publications
(239 reference statements)
3
218
0
8
Order By: Relevance
“…Second, source credibility is one of the constituents of trust, and higher levels of trust in a system's advice have been found to reduce advice discounting (Goodwin, GönĂŒl, & Önkal, 2013). Finally, if advisors feel that they are relatively less task-expert than the expert system, then we would expect less advice discounting (Rieh & Danielson, 2007).…”
Section: Expertise and Credibility Of System Forecastsmentioning
confidence: 99%
“…Second, source credibility is one of the constituents of trust, and higher levels of trust in a system's advice have been found to reduce advice discounting (Goodwin, GönĂŒl, & Önkal, 2013). Finally, if advisors feel that they are relatively less task-expert than the expert system, then we would expect less advice discounting (Rieh & Danielson, 2007).…”
Section: Expertise and Credibility Of System Forecastsmentioning
confidence: 99%
“…Credibility is a broad concept with many dimensions that has been studied in many scientific fields and. It is especially important when communicating messages (Rieh and Danielson 2007), which is also the domain we are interested in. We are concerned with actor credibility as a source of legitimacy to reward project On actor level and on consortium level:…”
Section: Credibilitymentioning
confidence: 99%
“…Most research on credibility focuses on website credibility [7,18,22,23], only few work addresses credibility of ANS. Kantowitz et al [12] showed that unreliable traffic information degrades the credibility of navigation systems.…”
Section: Background On Credibilitymentioning
confidence: 99%
“…Navigation is, and must remain, a secondary task in the driving context. Thus, credibility guidelines from other domains, such as website credibility [6,7,22,23], cannot be directly applied to ANS. Following the discussion in the previous section, we aim to enhance credibility by 1.…”
Section: Credibility Enhancing Interaction Designmentioning
confidence: 99%